Hypertensive Response to Exercise in Athletes: Unremarkable Finding or Relevant Marker for Future Cardiovascular Complications? - Laura Würzburger; Patrick Wiech; Valentina A. Rossi; Daniel Neunhäuserer; Stefano Caselli; Christian M. Schmied; David Niederseer (International Journal of Hypertension)
Background. In the general population, hypertensive response to exercise (HRE) predicts new-onset resting hypertension or other cardiovascular diseases. Methods. PubMed was searched for English articles published between January 1st 2000 and April 30th 2020. Additional studies were identified via reference lists of included studies. 92 papers were selected for full text analysis, finally 30 studies were included. Results. The results from 5 follow-up studies suggested an association between HRE and the risk of developing hypertension, while 10 studies reported a link with adverse cardiovascular events in the general population. Another study showed an association between HRE and future hypertension in athletes after a follow-up of 7 years. HRE in athletes was associated with left ventricular hypertrophy in three studies. Two other studies showed a link between HRE and focal myocardial fibrosis in triathletes and myocardial injury, respectively. One study found lower Apoliprotein-1 serum levels in athletes with HRE leading to a higher risk for cardiovascular disease. Only in one study no association with cardiovascular dysfunction in athletes with HRE was found. Conclusions. Based on current evidence, HRE is not a normal finding in athletes. If detected, it should be interpreted as a risk factor for future cardiovascular complications. Future research should address the adequate follow-up and management of athletes with HRE.